Knowledge Sharing Among Public Hospital Staff: An Extended UTAUT Study of Clinical Knowledge Exchange - Yul Kusmawati Tamrin; Ismanto Ismanto; Almansyah Rundu Wonua (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2025)
Clinical knowledge sharing in public hospitals is critical for patient safety, continuity of care, and service quality, yet it is often constrained by workload, fragmented information systems, and uncertainty about privacy and accountability. This manuscript develops an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model to explain staff intention to use approved digital communication tools for clinical knowledge exchange and the resulting exchange behavior. Beyond core UTAUT constructs (performance expectancy, effort expectancy, social influence, and facilitating conditions), the model incorporates task-technology fit, trust in digital communication, and perceived privacy and security risk. A quantitative cross-sectional design is proposed for public hospital settings using partial least squares structural equation modeling to test direct and indirect effects, with controls for profession, tenure, and technology experience. The study’s main contribution is a context-specific hypothesis set and an implementable measurement item bank for administrators seeking to strengthen organizational learning and digital governance in hospitals.